Private Infrastructure-A Bibliography : A Guide to World Bank Publications on Private Participation in Infrastructure - Karasapan, Omer (World Bank, Washington, DC, 2012)
The World Bank has well over 100 projects involving private participation in infrastructure (PPI) in its pipeline, the IFC has participated in 100 more PPI projects, and MIGA provides guarantees in support of such projects. In the course of this work, the Bank Group is amassing information on the legal, regulatory, institutional, and transactional issues confronting PPI projects in developing countries. The author provides a guide to the English-language publications and documents on PPI issues that the Bank Group has produced since 1992.